Computing across the curriculum: Design, implementing and evaluating an integrated approach to computational thinking - Whyte, Robert (2017)
This dissertation reports an exploratory design-based research study aimed at designing, implementing and evaluating an intervention to support hypertext writing through computational activities. The fieldwork comprised of four after-school computing sessions and involved participants in a series of activities designed to foster computational thinking and support the development of writing skills. Opportunities for writing to be supported through computational activities are explored through a feature analysis of student-generated hypertext projects, transcripts of classroom interactions, and researcher field notes. The results of the study are organised around the five design principles which informed the design and analysis of the intervention. These propose a learning environment which is: (i) integrated; (ii) constructive; (iii) collaborative; (iv) reflective, and; (v) scaffolded. The results show most participants could design, create, and evaluate interactive hypertext projects through a computational thinking environment. Results also point to the role of modelling strategies and support tools to scaffold learners as they create hypertexts in a computational environment. Accordingly, pedagogical recommendations proposed include the use of modelling strategies and scaffolded tools to support learners’ computational participation when constructing hypertexts. Likewise, methodological recommendations proposed include the use of design diaries to capture learners’ evolving ideas, when researching computational thinking environments.